IMPLEMENTATION OF THERAPEUTIC DRUG MONITORING IN INDONESIA - Sani, Aluwi Nirwana (STIKes Medistra Indonesia, 2021)
Therapeutic Drug Monitoring (TDM) is the clinical pharma cy practice of measuring plasma level of drugs. This service is required to optimize the drug therapy in individual patient and should be considered an adjunct to physician’s clinical judgment in assessing the course and the effectiveness of treatment, especially in critically ill patients. Indonesia has not been developed this service. Therefore, this article discus the roles and function of a best practice TDM service and how can this service be implemented in Indonesia.